The new external ion-beam station at the Demokritos Tandem 5.5 MV accelerator: A unique analytical tool in the fields of cultural heritage and environmental science - Sokaras, D.; et al., ... (HNPS Advances in Nuclear Physics, 2020)
At the 5.5 MV Tandem accelerator of the Institute of Nuclear Physics of NCSR Demokritos, Athens, a new external ion-beam set-up has been recently installed. The aim of this development was to establish a complete experimental set-up integrating the analytical capabilities of the PIXE, RBS and PIGE techniques, so that a complete elemental and near surface structural characterization of samples/artifacts to be attained in an almost non-destructive way and without any limitation concerning their size or conductive state. A careful 3D mechanical drawing optimized the experimental parameters of the set-up so that the special requirements imposed for optimum performance of the aforementioned techniques to be fulfilled.The first applications were focused in the quality control of tagged materials (technologically authentic replicas of attic ceramics and in coatings used by conservators for paintings).